Risk Factors of Stunting in Toddlers in The Village of Gunung Batin Udik, Lampung Tengah - Syahroni, Arfan; Yessiana Lutfia Bahri; Suci Kurnia Sarri (RADINKA JAYA UTAMA PUBLISHER, 2023)
Nutritional status in Indonesia, especially in toddlers is still a health problem, including malnutrition and stunting. Stunting is a linear growth disorder caused by chronic malnutrition or recurrent chronic infectious diseases. Risk Factors for chronic nutritional status in toddlers are not the same between regions, so this study aims to determine the risk factors for stunting in children under five in Gunung Batin Udik Village. This type of research was quantitative and the research design used observational analytics with a case-control approach. When this research was conducted on 5-20 November 2021 in Gunung Batin Udik Village, Terusan Nyunyai District, Central Lampung Regency in 2021. The population in this study were all toddlers of age 1-5 years old with a sample size of 120 respondents using simple random technique sampling. Data collection used questionnaires and observations then analyzed with the chi-square test. The results showed several risk factors for stunting events such as exclusive breastfeeding (OR: 2.704), mother's education level (OR: 3.455), mother's knowledge level (OR: 2.444), and family income (OR: 3.541). Whereas the fewer risk factors such as LBW (OR: 1,588), mother's employment status (OR: 2,093), latrine ownership (OR: 1,481), ownership of standard trash bins (OR: 0.576), and standard SPAL (OR: 0.619). Several factors are at risk for the incidence of stunting in infants.